Video-based surgical curriculum for open-globe injury repair, III: surgical repair - Siddiqui, Aliya; Weinert, Marguerite C.; Marando, Catherine M.; Begaj, Tedi; Lu, Yifan; Armstrong, Grayson W. (Digital Journal of Ophthalmology, 2022)
As one of the most severe forms of ocular trauma, open-globe injury (OGI) causes significant vision loss. Timely and meticulous repair of these injuries can improve patient outcomes. This video-based educational curriculum is intended to serve as an efficient yet comprehensive reference for OGI repair. We hope that these video-based articles help surgeons and trainees from around the world find answers to specific surgical questions in OGI management. The curriculum has been divided into six separate review articles, each authored by a different set of authors, to facilitate a systematic and practical approach to the subject of wound types and repair techniques. This third article highlights the use of antibiotics before, during, and after surgery; suture selection; surgical knots, and “ship-to-shore” suturing.